Anthropometric and clinical profile of students and its relationship with the metabolic syndrome in childhood - doi: 10.5020/18061230.2012.p202 - Paschoal, Mário Augusto (2012)
Objective: To evaluate the anthropometric and clinical profile of students and verify its association with the metabolic syndrome. Methods: The study involved 91 students, aged 7 to 8, attending public schools in Campinas-SP, Brazil. All students were submitted to an evaluation of blood pressure and anthropometrical parameters, focused on weight, height, abdominal and brachial circumferences measurements. To evaluate the incidence of metabolic syndrome among those children, they were divided into groups according to nutritional status and body mass index distribution. Results: 45 children (49.4%) were considered eutrophic, 12 were overweight (13.1%) and 34 were obese (37.3%). Comparisons between abdominal and brachial circumferences were statistically different for the eutrophic (55.5±3.5 and 18.6±1.3), overweight (62.9±4,0 and 21.4±1.7) and obese group (76.3±8.1 and 26.5±2.6). Systolic blood pressure was lower in the eutrophic group, compared to the obese one, with values of 88.2±4,0 and 93.4±7.2 mmHg, respectively. Both systolic and diastolic blood pressure were correlated to abdominal circumference values in all groups. However, only systolic blood pressure showed correlation with brachial circumference in all groups. Conclusion: Given the significant correlation observed between both systolic and diastolic blood pressure values and abdominal circumference values; as well as between systolic blood pressure values and brachial circumference, the anthropometric and clinical evaluation is to be considered suitable for early detection and to control the risk of development of metabolic syndrome among the children in this study